Composites of hierarchical metal–organic framework derived nitrogen-doped porous carbon and interpenetrating 3D hollow carbon spheres from lotus pollen for high-performance supercapacitors. (4th October 2017) - Xin, Lijun; Chen, Rongrong; Liu, Qi; Liu, Jingyuan; Li, Zhanshuang; Li, Rumin; Wang, Jun
Abstract : Nitrogen-doped porous carbon prepared via facile carbonization which displays high specific capacitance, is an excellent potential material for supercapacitors. Abstract : Composites (HPNCs/CS) of hierarchical metal–organic framework derived nitrogen-doped porous carbon (HPNC) and interpenetrating 3D hollow carbon spheres (CS) from lotus pollen are prepared via facile carbonization of Zn-metal–organic frameworks (ZIF-8) by controlling the appropriate temperature. In comparison with a single 3D hollow carbon sphere from lotus pollen, HPNCs/CS reduce the agglomeration of HPNCs and increase the specific surface area, and also promote electrical conductivity. In this work, HPNCs/CS materials exhibit high electrochemical performances with a high specific capacitance of 280 F g −1 in 6 M KOH electrolyte at a current density of 1 A g −1 . Moreover, the symmetric supercapacitor (HPNCs/CS//HPNCs/CS) exhibits a special energy density of about 16.2 W h kg −1 at a power density of 0.45 kW kg −1 in a wide voltage region of 0–1.8 V and a superb cycle stability (89.0% capacitance retention after 10 000 cycles) at 0.5 A g −1 . Such marked response in electrochemical behaviors shows that the HPNCs/CS//HPNCs/CS supercapacitor is a promising practical energy-storage material.